2017
DOI: 10.4336/2016.pfb.36.88.1261
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento inicial de Erythrina velutina sob restrição hídrica

Abstract: Erythrina velutina Willd. é uma espécie arbórea, nativa do nordeste brasileiro, utilizada como ornamental e empregada em programas de reflorestamento. Neste contexto, o objetivo deste trabalho foi obter informações sobre o desenvolvimento de E. velutina sob restrição hídrica. O experimento foi conduzido em delineamento inteiramente casualizado, em parcelas subdivididas no tempo, com quatro repetições. Foram utilizados dois manejos de irrigação (sem e com estresse hídrico). Aos 56 dias após o transplantio, as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
5
0
1
Order By: Relevance
“…Seedlings grown under the highest water restriction regime showed approximately 70% reduction in height and stem diameter (Figure 1A and 1B), as well as 50% reduction in the number of leaves when compared to the control treatment (Figure 1C). Analyzing the growth of Erythrina velutina seedlings De Oliveira et al, (2016) also observed reductions in height and number of leaves when grown under water restrictions. Reductions in cell division rates during periods of water restriction may imply a decrease in plant growth rate (Taiz et al, 2017).…”
Section: Resultsmentioning
confidence: 98%
“…Seedlings grown under the highest water restriction regime showed approximately 70% reduction in height and stem diameter (Figure 1A and 1B), as well as 50% reduction in the number of leaves when compared to the control treatment (Figure 1C). Analyzing the growth of Erythrina velutina seedlings De Oliveira et al, (2016) also observed reductions in height and number of leaves when grown under water restrictions. Reductions in cell division rates during periods of water restriction may imply a decrease in plant growth rate (Taiz et al, 2017).…”
Section: Resultsmentioning
confidence: 98%
“…The interruption of growth rates due to water unavailability is a reflection of the absence of this preceptor, which is intimately involved with the processes of growth and differentiation (Shao, Chu, Jaleel, & Zhao, 2008;Osakabe, Osakabe, Shinozaki, & Tran, 2014), and it is a response that depends on the volume of water lost, dehydration rate, and duration of stress (Bray, 1997). Reductions in growth rates in response to water deficits have been observed in some species occurring in Caatinga, such as Erythrina velutina Willd (Fabaceae) (Silva, Silva, Nogueira, & Albuquerque, 2010;Oliveira, Dombroski, Medeiros, & Medeiros, 2016), Poincianella bracteosa (Tul.) L.P. Queiroz (Fabaceae), and Libidibia ferrea (Mart.…”
Section: Discussionmentioning
confidence: 99%
“…As moringa has survival strategies under water restriction, mulungu (Erythrina velutina) seedlings have potential to develop xeromorphic characteristics, such as defoliation and greater root development. However, the seedlings production cannot be in water restriction conditions, so it can guarantee its better vegetative development (Oliveira et al, 2016).…”
Section: Discussionmentioning
confidence: 99%